Impact of smoking status on outcomes after concomitant aortic valve replacement and coronary artery bypass graft surgery - Saxena, A.; Shan, L.; Dinh, D.; Reid, Christopher; Smith, J.; Shardey, G.; Newcomb, A. (2014)
Background There is a paucity of data on the impact of smoking status on outcomes after concomitant aortic valve replacement and coronary artery bypass graft (AVR-CABG) surgery. Methods Data obtained prospectively between June 2001 and December 2009 by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons National Cardiac Surgery Database Program were retrospectively analyzed. Demographic and operative data were compared between patients who were nonsmokers, previous smokers, and current smokers using chi-square test and t-test. The independent impact of smoking status on 14 short-term complications and long-term mortality was determined using binary logistic and Cox regression, respectively. Results Concomitant AVR-CABG surgery was performed in 2,563 patients; smoking status was recorded in 2,558 (99.8%) patients. Of these, 1,052 (41.1%) patients had no previous smoking history, 1,345 (52.6%) patients were previous smokers, and 161 (6.3%) patients were current smokers. The 30-day mortality rate was 3.5% in nonsmokers, 4.1% in previous smokers, and 3.1% in current smokers (p = nonsignificant). The incidence of perioperative complications was similar in the three groups. The mean follow-up period for this study was 36 months (range, 0-105 months). After adjusting for differences in patient variables, the incidence of late mortality was higher in previous smokers (hazard ratio [HR], 1.44; 95% confidence interval [CI], 1.14-1.81; p = 0.002) compared with nonsmokers. A trend toward increased late mortality in current smokers was noted (HR, 1.34; 95% CI, 0.86-2.08; p = 0.201). Conclusion Smoking is not associated with adverse outcomes after concomitant AVR-CABG surgery. Smoking status should not, therefore, preclude these patients from undergoing this procedure. Given the adverse effect of smoking on overall cardiovascular morbidity and mortality and late postoperative mortality, patients should be encouraged to quit smoking. © 2014 Georg Thieme Verlag KG Stuttgart New York.